Acute and Late Toxicity In Breast Cancer Patient That Received Hypofractionated Adjuvant Radiotherapy after Breast Conserving Surgery: A Case Report - Sinta Prastiana Dewi; Henry Kodrat (Indonesian Journal of Cancer, 2020)
Introduction: Breast cancer is the most common female malignancy worldwide. Breastconserving surgery followed by adjuvant radiotherapy is a preferable treatment option. Hypofractionated radiotherapy is an attractive fractionation scheme because of its shorter treatment duration. This paper aims to report the short-term and long-term toxicity of hypofractionated radiotherapy in breast cancer patients at our institution. Case Presentation: A 58-year-old woman with right breast cancer T2N1M0 had undergone breast-conserving surgery with axilla lymph node dissection. This patient underwent adjuvant whole breast radiotherapy with a dose of 42.56 Gy in 16 fractions followed by tumor bed boost with a dose of 16 Gy in 8 fractions. After undergoing the fourth fraction of boost, she had hyperpigmentation on her radiation area (RTOG skin toxicity grade 1). At the 6-month follow-up, the hyperpigmentation still appeared. Until the 24-month follow-up, after she completed radiotherapy, there was no sign of tumor recurrence and toxicity.Conclusion: Hypofractionated radiotherapy could be an option for breast cancer treatment that provides equivalent local control, survival, and side effects to conventional fractionation radiotherapy.